Sociodemographic Factors Associated with Chronic Obstructive Pulmonary Disease Comorbidities: Based on Indonesia Family Life Survey-5 - Wardatul Jannah; Adi Nurmesa (LPPM Universitas Abdurrab, 2024)
COPD is still one of the major health problems in Indonesia. The aim of this study was to look at the relationship between sociodemographics and the incidence of comorbidities in COPD patients. Cross-sectional study design, using IFLS-5 data. Inclusion criteria were patients with a diagnosis of COPD by self-report, and at least 15 years old. Results: Of 34,252 people filling out household health questionnaires in IFLS 5, 618 subjects had COPD. Based on multivariate test, gender (aOR: 1.792 (1.282-2.506); p-value: 0.001), age 36-45 years (aOR: 1.259 (0.764-2.074); p-value: 0.028), age 46-55 years (aOR: 2.418 (1.365-4.282); p-value: 0.002), age 56-65 years (aOR: 2.418 (1.365-4.282); p-value: 0.002), and age >65 years (aOR: 3.502 (1.884-6.510); p-value: 0.000). 002), age 56-65 years (aOR: 3.502 (1.884-6.510); p-value: 0.000), and age >65 years (aOR: 6.508 (3.338-12.690); p-value: 0.000) had a significant association with the incidence of comorbidities in COPD patients in Indonesia.